TEMPORAL AND SPATIAL DISTRIBUTION OF ARTHTROPODA IN PLANTS Wedelia trilobata, Vigna sp. And Heliotropium indicum L - Muhammad Zulhariadi (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2018)
The purpose of this research was to determine the spatial and temporal distribution of arthtropoda in plants Wedelia trilobata, Vigna sp. and Heliotropium indicum L. This research is an explorative descriptive study conducted by direct observation of taxa and the number of arthropod individuals found in various types of wild plants in the rice field area Tegal Gondo. Data analysis in this study used descriptive analysis to calculate the spatial and temporal distribution of Arthropoda at each sampling point. The results showed that in the spatial distribution, species diversity of arthropod species was highest in Vigna sp. and Heliotropium indicum L. which amounts of each was 16 species and is ± 20 m from the paved road, while the Widelia trilobata flower is 14 species and is ± 15 m from the paved road. In temporal distribution, arthropods abundance in morning measurements that is highest in the Wedelia trilobata was 16.66 individuals/m2 while in most daytime measurements on the Wedelia trilobata plant of 9.77 individuals/m2, and on the measurement in the early evening most on Wedelia trilobata and Vigna sp. of 1.22 individuals/m2.